2011
DOI: 10.1080/10888705.2011.527598
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Zoo Visitors on the Fecal Cortisol Levels and Behavior of an Endangered Species: Indian Blackbuck (Antelope cervicapra L.)

Abstract: This study investigated behavioral activities (resting, moving, aggressive, social, and reproductive behavior) and fecal cortisol levels in 8 individually identified adult male blackbucks during periods of varying levels of zoo visitors (zero, low, high, and extremely high zoo visitor density). This study also elucidated whether zoo visitor density could disturb nonhuman animal welfare. This study analyzed fecal cortisol from the samples of blackbuck by radioimmunoassay and found significant differences (p < .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
2
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 51 publications
6
36
2
2
Order By: Relevance
“…These findings are in line with results from several other studies, e.g., with blackbucks (Antelope cervicapra: Rajagopal et al 2011) and with spider monkeys (Ateles geoffroyii rufiventris: Davies et al 2005). Urinary cortisol concentrations (but not saliva cortisol concentrations) likewise increased significantly with higher visitor number in captive orangutans at Chester Zoo (Wehnelt et al 2004).…”
Section: Effect Of Visitors On Stress Indicatorssupporting
confidence: 82%
“…These findings are in line with results from several other studies, e.g., with blackbucks (Antelope cervicapra: Rajagopal et al 2011) and with spider monkeys (Ateles geoffroyii rufiventris: Davies et al 2005). Urinary cortisol concentrations (but not saliva cortisol concentrations) likewise increased significantly with higher visitor number in captive orangutans at Chester Zoo (Wehnelt et al 2004).…”
Section: Effect Of Visitors On Stress Indicatorssupporting
confidence: 82%
“…The decreased inactivity in the pigs in this study is similar to findings of increased activity under conditions of greater visitor pressure in zoo-housed gaur (Sekar et al, 2008), and blackbuck (Rajagopal et al, 2011). Conversely both of these species, and also gazelles (Mansour et al, 2000), showed higher aggression under the same conditions, whereas the pigs in this study showed lower aggression.…”
Section: The Presence Of Visitors Affects Vietnamese Pot-bellied Pig supporting
confidence: 73%
“…Some felids, for example, appear to show little or no behavioural response to visitors (Margulis et al, 2003, O'Donovan et al, 1993, whereas other studies report a visitor density influence on the behaviour of zoo-housed cats Chellam, 2002, Sellinger andHa, 2005). Ungulates have not been widely studied in this context, but sika deer (Cervus nippon; Shen-Jin et al, 2010) and Soemmerring's gazelle (Gazella soemmerringii; Mansour et al2000) both show increased alertness as visitor density increases, and higher levels of aggression have been found in gaur (Bos gaurus gaurus; Sekar et al, 2008) and blackbuck (Antilope cervicapra; Rajagopal et al, 2011) when visitor pressure is high.…”
mentioning
confidence: 99%
“…The literature on captive animals indicates that fear-provoking stimuli may lead to redirected behaviours such as aggression and abnormal behaviours (Mason, 1991;Olsson et al, 2011), behaviours that are likely associated with a range of negative emotions, such as frustration and anger (Broom and Johnson, 1993;Mellor, 2012;Van Loo et al, 2003). Interestingly, increases in intra-group aggression under high visitor numbers has been reported in a range of species including Indian gaur (Sekar et al, 2008), ring-tail lemurs (Chamove et al, 1988), Indian blackbuck (Rajagopal et al, 2011) and gorillas (Wells, 2005).…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies on other species have demonstrated that visitors may compromise animal welfare in zoos (Davis et al, 2005;Hosey, 2013). For example, visitors have been associated with increased levels of aggression in Indian blackbuck (Rajagopal et al, 2011), decreased levels of affiliative behaviour in cotton-top tamarins (Chamove et al, 1988) and less time visible to the public in jaguars (Sellinger and Ha, 2005). However, we are unaware of any published studies that have investigated the impact of human presence on the welfare of penguins in zoos.…”
Section: Introductionmentioning
confidence: 90%